Public Problem Characterization, Policy Solution Generation, and Intra‐Agenda Connectivity. Issue 4 (29th April 2016) - Liu, Xinsheng; Robinson, Scott; Vedlitz, Arnold
Abstract : While policy agenda studies have extensively examined the interplays of various venues, one under‐explored area is the internal dynamics within an agenda venue. In this study, we focus on one of the important venues—news media—and investigate the inherent connections between how a public problem is characterized and how problem solutions are generated in media agenda setting. Drawing on agenda‐setting theories, we develop a typology to theorize the relationships between problem characterization and solution advocacy, and use a news dataset on climate change to empirically assess how issue characterization affects issue solution generation. Our logistic regressions demonstrate that the likelihoods of climate change policy solutions being proposed in the news are significantly influenced by how the media stories characterize the issue along four key attribute dimensions: issue image, scope, linkage, and narrative style. Key implications are discussed in the conclusion.